Which kinds of social safety net transfers work best for the ultra poor in Bangladesh? Operation and impacts of the transfer modality research initiative - Ahmed, Akhter; Hoddinott, John F.; Roy, Shalini; Sraboni, Esha; Quabili, Wahid; Margolies, Amy (International Food Policy Research Institute, 2020)
This report presents the results of the TMRI evaluation. It is organized in ten sections. The rest of Section 1 presents the objectives of the study, conceptual issues and empirical evidence of the effects of food and cash transfers. Section 2 describes the salient features of the TMRI. Section 3 discusses the analytical methodology and the data used in the empirical work. Section 4 gives a profile of survey households. Section 5 provides the findings of evaluation of the TMRI implementation process, assesses various aspects of participation in the TMRI, and provides the cost analysis results. Section 6 presents the impact of the TMRI on household consumption. Section 7 shows impact of the TMRI on maternal knowledge and practices related to child nutrition. Section 8 provides the impact of the TMRI on child anthropometric status. Section 9 presents case studies 3 of TMRI participants from qualitative research. Section 10 summarizes the main findings and provides policy conclusions.